Not quite what it seems: rethinking the way we view teachers’ beliefs and practices – a case study of a Malaysian ESL teacher - Jerome, Collin; Samuel, Moses Stephens Gunams (Penerbit Universiti Kebangsaan Malaysia, 2017)
Research has shown that there is high congruity between pedagogical beliefs and classroom practices among expert teachers and how this demarcates them from their novice counterparts. However, this is not necessarily true for all experts and novices in the profession because their individual differences affect the degree of congruity and this has caused revisions in the ways which the expert-novice divide is understood. This paper examines belief-practice congruity and expert-novice differences through a case study of a novice Malaysian ESL teacher. The teacher’s beliefs about teaching and learning were obtained via a two-part questionnaire, while the classroom practices were analysed based on permitted recordings of her lessons. The findings reveal a convergence between the teacher’s classroom practices and her personal beliefs about teaching and learning, as well as the teacher’s role in the ESL classroom. The findings also reveal the teacher’s classroom practices, especially her use of error correction techniques, mirrored those of expert teachers. It was also found that the teacher’s own perceptions of student learning, her teaching experience and the realities of her classroom have shaped her beliefs and influenced her practices. The findings may not only provide useful insights into beliefpractice congruity as experienced by novice ESL teachers, but also imply the need for increased awareness of expert and novice teachers’ individual differences which have direct consequences on instruction and learning.